Optimalisasi Kepekaan Indra Siswa Tuna Netra dalam Materi Pengenalan Ayam: Suatu Tahapan Perencanaan di Sekolah luar Biasa - Damayanti, Nia Wahyu; Jatmiko, Henry Trias Puguh; Holipah, Holipah; Pratama, Fungki Adi; Dariyati, Irah Praba; Prihastuti, Dina; Lusia, Rilika; Bachtiar, Abdul Hamid (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2023)
Planning is one of the most important stages in designing a lesson. At this stage, learning objectives, the material to be taught, learning media, and assessments are formulated. This qualitative descriptive research involves teachers, school principals, and various parties to carry out lesson plans. The material focused on in this lesson plan is material regarding the introduction of chickens to blind students. Generally, at this planning stage, the teacher carries out global planning, such as learning materials and objectives. Then determine the learning media used, then find and make learning media and prepare everything needed during learning. In this lesson, the media used are chicks and miniature chicks. With various considerations regarding student safety, the teachers chose chicks as the media used in this lesson. Good planning makes student learning experiences more structured, directed, and effective. Teachers can better adapt learning to student needs, increase engagement and motivation, and improve learning outcomes. The conclusion from the planning stage (Plan) in special schools on introducing chickens for blind students is at the planning stage of adapting the curriculum to the needs and characteristics of blind students. The main focus when developing learning designs for students with special needs, including students who are blind. Chicken introduction materials must be designed with an innovative and accessible approach for blind students. The designed learning objectives include aspects of knowledge about chickens, understanding of their characteristics, and details of chicken components. At this planning stage, audio-based early learning activities for students were also designed, such as the sound of chickens, natural situations, waves, and so on, which can lead to the core of learning.